Gangguan Kecemasan Pada Tokoh Cath Dalam Novel Fangirl Karya Rainbow Rowell - Fadlah Wulansani (PENAOQ: Jurnal Sastra, Budaya dan Pariwisata, 2022)
This research is entitled Anxiety Disorders in Cath Characters in Rainbow Rowell's Fangirl Novel. The purpose of this study is to describe anxiety disorders in the character Cath in the novel Fangirl by Rainbow Rowell. The method that will be used is descriptive qualitative method. The theory that will be used focuses on the Psychoanalytic theory by Sigmund Freud, using the concepts of consciousness and the unconscious mind. The result of this study is that anxiety disorders have the concept of awareness and unconsciousness of a person's mind that can affect the way he faces reality.